FVC, FEV1 And FEV1/FVC% In Type-1 Diabetic Male And Their Relationships With HbA1c - Arif, Khan Mohammad; Jahan, Nasim; Sultana, Nayma; Akter, Rezina (Journal of Bangladesh Society of Physiologist, 2012)
Background: Diabetes mellitus is a chronic and debilitating disease. Its complications give rise to micro and macrovascular diseases which affect eyes, kidneys, heart, blood vessels, nerves and also lungs. There may be a relationship between type-1 diabetes and reduced lung function. Objectives: To observe FVC, FEV1, FEV1/FVC % and their relationship with HbA1C in type-1 diabetic male in Bangladesh. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from January to December 2009. A total number of 60 male subjects, from 18-30 years of age was taken and was divided into control and study groups. Among them study group was consisted of 30 type-1 diabetic male patients. Control group was consisted of 30 apparently healthy age, sex, BMI and socioeconomic status matched non-diabetic subjects. All the subjects belonged to lower socio-economic status. For assessment of lung function, FVC, FEV1, FEV1/FVC % of all the subjects were measured. All of theses tests were done by spirometric method by using a digital Spirometer. Again, to observe glycemic control of blood, glycosylated hemoglobin (HbA1c) levels of diabetic patients were also measured by usual laboratory technique. Data were analyzed by Independent-Samples t test and Pearsons correlation coefficient test as applicable. Results: FVC (p <0.001), FEV1 (p < 0.001), and FEV1/FVC% (p < 0.05) were significantly lower in type-1 diabetic patients in comparison to those of apparently healthy non-diabetic male. Again FVC and FEV1 had significant (p < 0.001) negative correlation but FEV1/FVC% had non-significant positive correlation with HbA1c. Conclusion: Impairment of some lung functions may be found in type-1 diabetic male which may be due to poor glycemic control. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11156 J Bangladesh Soc Physiol. 2012, June; 7(1): 23-28